ANTI-INFLAMMATORY EFFECT OF ELETTARIA CARDAMOM OIL ON CARRAGEENAN-INDUCED PAW EDEMA USING RATS BASED ON TUMOR NECROSIS FACTOR Î±, INTERLEUKIN 6, AND INTERLEUKIN 1 LEVELS IN SERUM - Sermugapandian, Nithya; R, Rubini; V, Martina (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: In this study, we evaluated the anti-inflammatory effect of Elettaria cardamom oil and the underlying mechanism using in vivo models of inflammation. Methods: Male Spragueâ€“Dawley rats, 4-6 weeks old, weighing 120-130 gms are used for the study. The anti-inflammatory study of E. cardamom oil was studied by injecting 0.1 ml of 1% carrageenan to the subplantar region of the right hind paw of rats. The development of acute inflammation was measured at the end of every 1st, 2nd, 3rd, 4th, 5th, and 6th h using plethysmometer. Results: As results from the above study, E. cardamom oil at a dose of 0.175 ml/kg was less significant than that of E. cardamom oil at a dose of 0.280 ml/kg when given orally. A p<0.05 shows a significant decrease in paw edema. It also reduced the levels of pro-inflammatory cytokines such as tumor necrosis factor Î±, interleukin (IL) 1, and IL 6 levels in the serum. The histopathology results also showed a significant reduction of congested blood vessels with no marked impression for inflammation. Conclusion: E. cardamom oil possesses anti-inflammatory activity in dose-dependent manner as they inhibit the levels of pro-inflammatory cytokines.